The Effect Of Capital Structure And Company Size On Company Value At Pt Mayora Indah Tbk 2014-2023 Period - Alfitra, Hafiz; Kharisma, Indri (Fin Sinergy: Jurnal Manajemen Keuangan, 2025)
The purpose of this study is to determine the financial performance of PT Mayora Indah Tbk for the 2014-2023 period by analyzing its financial statements. Financial performance can be assessed through various factors. In this study, three variables were used: capital structure, proxied by the Debt to Equity Ratio (DER), company size, proxied by Size, and company value, proxied by Price to Book Value (PBV). This study uses a quantitative method, with secondary data obtained from the company's official website.https://www.mayoraindah.co.id/. Data analysis techniques using Normality Test, Multicollinearity Test, Autocorrelation Test, Heteroscedasticity Test, Multiple Linear Regression Test, Correlation Coefficient Test, Determination Coefficient Test, t-test, and F-test using SPSS software version 27. The results of this study indicate partially, it was found that Debt to Equity Ratio (DER) does not significantly affect Price to Book Value (PBV). With a significance of 0.889> 0.05 and t count 0.145 0.05. The R square value obtained is 0.053 which shows that Debt to Equity Ratio (DER) and Size have an effect of 5.3% on Price to Book Value (PBV), besides that the remaining 94.7% is influenced by other variables that have not been examined in this study